GAMBARAN KEJADIAN BBLR DI RSUD H.A.SULTHAN DAENG RADJA KABUPATEN BULUKUMBA - Nurhidayah; Tenriwati; Fitriani (Jurnal Kesehatan Panrita Husada, 2019)
Low birth weight babies (LBW) are babies born weighing less than 2500 grams regardless of gestational period (birth weight is the weight of the baby weighed within 1 hour after birth). LBW is a human individual who is due to weight, gestational age, and causes of birth are less than the standard birth of a normal baby. From the results of the study conducted by researchers on July 19, 2018 on 47 respondents, who experienced LBW as many as 29 babies while the normal number of 18 babies. The purpose of this study was to know the picture of the incidence of Low Birth Weight Babies (LBW) in HA Sulthan Hospital Daeng Radja Bulukumba District in 2018.The research method uses a descriptive design with a simple approach. Sampling is done by nonprobability sampling technique with incidental sampling approach. The population in this study were 307. The sample in this study were 30 respondents.The results showed that mothers who gave birth at age 20-35 years were 6 people 20.0%, and aged <20 and> 35 as many as 24 people 80.%, good nutritional status as many as 27 people 90.0%, nutritional status less than 3 people 10%, consumption Fe tablets are as much as 16 people 53.3%, consume less tablet fe as many as 14 people 46.7%, gestational periods are not as risky as 21 people70%, high risk 9 people 30%, paritasibu low risk as many as 22 people 73.3%, high risk 8 26.7% people. Routine antenatal care examination as many as 29 people 96.7%, non-routine 1 person 3.3%, the conclusion in this study was the infants who experienced LBW in H.Andi Sulthan Daeng Radja Hospital Bulukumba District in 2018 of 30 infants who experienced LBW caused by several factors, namely nutritional status, gestational period, age, parity and ANC examination. It is recommended for mothers to increase the source of information regarding LBW.